Accountability and short-termism: some notes on loyalty shares. (2nd January 2015) - Delvoie, Jeroen; Clottens, Carl
Abstract : This article discusses so-called "loyalty shares" (ie shares granting certain rewards such as extra dividends or voting rights to shareholders that hold their shares for a specified period of time) as a means of addressing short-termism in financial markets. Loyalty shares have been hotly debated in international policy circles recently. We review the experience with loyalty shares in a number of EU Member States and discuss the state of play at the EU level. In conclusion, we see little harm in letting companies and Member States experiment with loyalty shares and thereby putting them – somewhat ironically – to the market test.